Facing Death with a Smile: Study on Islamic Counseling in the Da'wa of KH Imam Syairozi Indonesia - Thohir, Mohamad; Hidayat, Rahmat (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
Death is usually considered a frightening specter by most people, so any effort is made to achieve a healthy life,